A facile fabrication method for ultrathin NiO/Ni nanosheets as a high-performance electrocatalyst for the oxygen evolution reaction. Issue 30 (28th March 2017) - Xu, Yushuai; Huang, Kai; Ou, Gang; Tang, Hao; Wei, Hehe; Zhang, Qingyun; Gong, Jianghong; Fang, Minghao; Wu, Hui
Abstract : A facile method to fabricate NiO/Ni nanosheets in large yield by repeated size reduction and thermal oxidation has been developed. Abstract : In order to realize the oxygen evolution reaction (OER) with high efficiency on a large scale, a facile method has been created to fabricate NiO/Ni nanosheets by repeated size reduction and thermal oxidation on the surface. By using ultrathin Ni nanosheets with thicknesses of around 4 nm and different temperatures of thermal treatment, tunable oxidation of the metallic nanosheets was achieved. This was proven to have a great impact on the catalysts' electrical conductivity and activity. The NiO/Ni two-dimensional (2D) nano-metal catalyst prepared at 250 °C possesses a potential of 1.59 V ( vs. RHE) at the current density of 100 mA cm −2 in 1 M KOH solution, and still exhibits a high performance after 15 000 cycles. Furthermore, the enhanced electrical conductivity and exposure of active sites contribute to a kinetically low-cost process, resulting in a Tafel slope of 51 mV dec −1 . The repeated folding and calendering method is a mature industrial manufacturing procedure, and therefore this creative repeated size reduction and thermal oxidation production process for oxide/metal nanosheets has the potential to be extended to various kinds of metal materials that could be used to produce electrocatalysts in high yields.